Adobe Dreamweaver CS3 how-tos : 100 essential techniques - Karlins, David (AdobePress, 2007)
Adobe Dreamweaver CS3 is more than just the world's most popular and powerful Web design tool: As part of Creative Suite 3 (which includes Photoshop CS3 and Flash CS3), it's a key component of an overall Web design workflow that encourages users to rely on all of their applications to seamlessly create graphically rich content for the Web and motion graphics. This information- and image-packed guide lets users get right down to work by focusing on the Dreamweaver CS3 features they're most likely to use, including Spry framework for Ajax and Spry widgets and effects, and Absolute Placement objects; the book showcases each in a stand-alone tip, complete with a relevant hint or two and helpful screenshot. This is how readers can learn just what they need to know, exploring the program at their own pace, exploring just the features and tools they need.